IMMOBILISATION OF COPPER (I) OXIDE/ZINC OXIDE NANOPARTICLES ON THE GAS DIFFUSION LAYER FOR CO2 REDUCTION REACTION APPLICATION - Yasin, Nor Hafizah; Yahya, Wan Zaireen Nisa (Malaysian Journal of Science, 2024)
The electrochemical reduction of carbon dioxide (CO₂RR) represents a promising strategy for CO₂ mitigation, requiring highly efficient catalysts integrated into electrochemical devices to achieve high conversion rates and energy efficiencies for desired products. Establishing a gas diffusion electrode is crucial for practical applications of CO₂ electrochemical reduction reactions (CO₂RR). This study uses the air-spraying method to immobilise nano-catalysts onto a gas diffusion layer (GDL) with exceptional homogeneity. A composite of copper(I) oxide (Cu₂O) and zinc oxide (ZnO) nanoparticles in a 4:1 ratio was deposited onto the GDL. Surface morphology analysis revealed the successful immobilisation of cubic Cu₂O and hexagonal wurtzite ZnO with a uniform distribution, indicating potential improvements in CO₂RR performance. Contact angle measurements were conducted to assess surface hydrophobicity, comparing pristine GDL with Cu₂O/ZnO-based GDL. Although the contact angle on the surface of the Cu₂O/ZnO-based GDL slightly reduced from 143.69° to 134.82°, it maintained its hydrophobic nature. This reduction is attributed to Nafion, a binder in the catalyst ink mixture. The sustained high contact angle is crucial for the CO₂ reduction reaction process. X-ray diffraction (XRD) diffractograms of Cu₂O/ZnO-based GDL were compared with reference Cu₂O, ZnO, and bare GDL. The presence of all essential peaks confirms the successful immobilisation. The air-spraying technique effectively achieved a favourable distribution of active metals.